Passiflora edulis Leaf Extract: Evidence of Antidiabetic and Antiplatelet Effects in Rats - Correa Salles, Bruno Cesar; Silva, Marcelo Aparecido da; Taniguthi, Lara; Ferreira, Juliane Naiara; Rocha, Claudia Quintino da; Vilegas, Wagner [UNESP]; Dias, Pollyana Hammoud [UNESP]; Pennacchi, Paula Comune; Silveira Duarte, Stella Maris da; Rodrigues, Maria Rita; Pereira Lima Brigagdo, Maisa Ribeiro; Ardijo Paula, Fernanda Borges de (Pharmaceutical Soc Japan, 2020)
Different Passiflora species have been appointed as a promising herbal medicine due to antioxidant properties; however, their effect on oxidative process induced by diabetes is still controversial. We aimed to evaluate effects of hydroethanolic extract 70% from P. edulis leaf on biochemical blood markers, collagen glycation, production of oxidant species and platelet aggregation in diabetic rats. The phytochemical analysis of the extract was performed by dereplication using LC coupled to the Photodiode Array Detector and Mass Spectrometer detector. Male Wistar rats were assigned to the control group and groups treated with alloxan (150 mg/kg) intraperitoneally, extract (200 mg/kg/d, for 90d) and combination of alloxan and extract. The phytochemical analysis suggested the presence of flavonoids C-glycosides in the extract. The diabetic animals treated with the extract presented improvement in glycaemic control, reduced glycation collagen, levels of non-high density lipoprotein (non-HDL) cholesterol, total cholesterol and creatinine, production of oxidant species and aggregation in platelet in relation to diabetic animals non-treated. Our results showed that P. edulis leaf extract presents a health benefit to the diabetic state, preventing the appearance of its complications. Its effect can be associated with flavonoids, among which is the flavonoid C-glycoside isoorientin.
Keywords: Passiflora edulis; diabetes mellitus; platelet aggregation; biochemical marker; quantification; isoorientin